Government spending on regional public services in Greece: Spatial distribution of their evolution before and during the economic crisis - Eugenia Anastasiou; Theodossiou George; Thanou Eleni (European Regional Science Association (ERSA), 2015)
Greece is still caught in a prolonged recession, which started in 2008. As a result, the economy continues to shrink, which has direct repercussions on the level of private and public consumption as well as on the level government's functions. The present paper attempts to record and depict spatially the evolution of the per capita public spending of the central government on regional services. The specific category of public spending represents a measure of relative welfare as well as a measure of regional development. For the purposes of the research we applied analytical methods such as descriptive statistics and we used specialized mapping analysis programs and geographical information systems (GIS). The evolution over time is observed on the basis of the annual percentage changes of per capita spending. The period of analysis is 2008-2013 and it includes years before the manifestation of the economic crisis as well as the years of the crisis' peak. The thematic maps that were constructed on the basis of the data clearly demonstrate that government spending on the regions was dramatically reduced during the crisis while the period during which the tightening of fiscal policy had a direct impact on the regions stands out. The crisis does not allow any opportunity for development on the majority of the Greek prefectures.
Keywords: 330; financial crisis; public expenditures; regional public services; spatial distribution